Genome-wide identification and analysis of B-BOX gene family in grapevine reveal its potential functions in berry development - Wei, Hongru; Wang, Peipei; Chen, Jianqing; Li, Changjun; Wang, Yongzhang; Yuan, Yongbing; Fang, Jinggui; Leng, Xiangpeng (BMC plant biology, 2020)
Background The B-BOX (BBX) proteins are the class of zinc-finger transcription factors and can regulate plant growth, development, and endure stress response. In plants, the BBX gene family has been identified in Arabidopsis , rice, and tomato. However, no systematic analysis of BBX genes has been undertaken in grapevine. Results In this study, 24 grapevine BBX ( VvBBX ) genes were identified by comprehensive bioinformatics analysis. Subsequently, the chromosomal localizations, gene structure, conserved domains, phylogenetic relationship, gene duplication, and cis -acting elements were analyzed. Phylogenetic analysis divided VvBBX genes into five subgroups. Numerous cis -acting elements related to plant development, hormone and/or stress responses were identified in the promoter of the VvBBX genes. The tissue-specific expressional dynamics of VvBBX genes demonstrated that VvBBXs might play important role in plant growth and development. The transcript analysis from transcriptome data and qRT-PCR inferred that 11 VvBBX genes were down-regulated in different fruit developmental stages, while three VvBBX genes were up-regulated. It is also speculated that VvBBX genes might be involved in multiple hormone signaling (ABA, ethylene, GA3, and CPPU) as transcriptional regulators to modulate berry development and ripening. VvBBX22 seems to be responsive to multiple hormone signaling, including ABA, ethylene GA3, and CPPU. Some VvBBX genes were strongly induced by Cu, salt, waterlogging, and drought stress treatment. Furthermore, the expression of VvBBX22 proposed its involvement in multiple functions, including leaf senescence, abiotic stress responses, fruit development, and hormone response. Conclusions Our results will provide the reference for functional studies of BBX gene family, and highlight its functions in grapevine berry development and ripening. The results will help us to better understand the complexity of the BBX gene family in abiotic stress tolerance and provide valuable information for future functional characterization of specific genes in grapevine.